2017
DOI: 10.21107/jaffa.v5i2.3765
|View full text |Cite
|
Sign up to set email alerts
|

Tax Aggressiveness Seen From Company Characteristics and Corporate Social Responsibility

Abstract: <pre>This study aims to analyze the effect of company characteristics and Corporate Social Responsibility on tax aggressiveness. Dependent variable used in this research was tax aggressiveness as measured by effective tax rate. The independent variables in this study were company characteristics consisting firm size, leverage, and capital intensity. This study also used Corporate Social Responsibility as independent variable. The sample was 41 companies with the research period for 5 years (2011-2015) se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
5
0
12

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 8 publications
4
5
0
12
Order By: Relevance
“…Bank size and profitability had a significant and negative effect on ETR. This finding also confirmed result found by Ngadiman & Puspitasari (2014); Harjito et al (2017) that profitability and bank size had significant impact on tendency of conducting tax avoidance. The larger the banks and the better the profitability of the banks, the smaller the ETR will be, which means that the possibility of tax avoidance by the banks was greater.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Bank size and profitability had a significant and negative effect on ETR. This finding also confirmed result found by Ngadiman & Puspitasari (2014); Harjito et al (2017) that profitability and bank size had significant impact on tendency of conducting tax avoidance. The larger the banks and the better the profitability of the banks, the smaller the ETR will be, which means that the possibility of tax avoidance by the banks was greater.…”
Section: Discussionsupporting
confidence: 89%
“…Although banks were allowed flexibility to operate at DER exceeding four to one (4:1), the banks sample could not execute tax avoidance aggressively although they have higher DER as MFD-169 stated. This result was also supported by the previous researches Kurniasih and Sari (2013), Ngadiman & Puspitasari (2014), and Harjito et al (2017) that found DER did not have any impact on tax avoidance because the firms could not maximize the benefit from maximization of using debts. This result was contrast with the agency theory explained by Jensen & Meckling (1976) because the conflict of interest between company and the government did not arise significantly since the tax paid by the companies is above 25% on average.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Manajemen berperan penting dalam memilih strategi perusahaan khususnya untuk memperbanyak kekayaan perusahaan. Manajemen cenderung melakukan agresivitas pajak dalam usahanya untuk mengurangi beban pajak yang perlu dibayarkan (Harjito, Sari, & Yulianto, 2017).…”
Section: Pendahuluanunclassified